2006
DOI: 10.1519/r-17254.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistance Training on the Physical Capacities of Adolescent Soccer Players

Abstract: This study examined the effects of a progressive resistance training program in addition to soccer training on the physical capacities of male adolescents. Eighteen soccer players (age: 12-15 years) were separated in a soccer (SOC; n = 9) and a strength-soccer (STR; n = 9) training group and 8 subjects of similar age constituted a control group. All players followed a soccer training program 5 times a week for the development of technical and tactical skills. In addition, the STR group followed a strength trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
129
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(154 citation statements)
references
References 0 publications
14
129
1
10
Order By: Relevance
“…21 Studies examining changes in speed and COD ability in soccer players after RT, plyometric, and other interventions alone or in combination report contrasting findings. 22,23 The lack of changes in the present study might also be a result of the short intervention duration. For example, Michailidis et al 24 found that only after 12-weeks of plyometric training did 30m-sprint time reduce by 3%.…”
Section: Discussionmentioning
confidence: 76%
“…21 Studies examining changes in speed and COD ability in soccer players after RT, plyometric, and other interventions alone or in combination report contrasting findings. 22,23 The lack of changes in the present study might also be a result of the short intervention duration. For example, Michailidis et al 24 found that only after 12-weeks of plyometric training did 30m-sprint time reduce by 3%.…”
Section: Discussionmentioning
confidence: 76%
“…The between-day reliability of commonly used strength tests in youth athletes has yet to be reported, despite a plethora of research evaluating strength in this cohort (3,7,(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…The training programs for this study were based on available data sources [4,11,13,24,25] that used both children and adolescents who were either non-athletes or athletes. As our resistance training programs were predominantly designed to evaluate how young Thai male athletes respond to the program, subjective information revealed that young Thai male athletes were highly capable of performing all exercise routines throughout the two weeks of study.…”
Section: Discussionmentioning
confidence: 99%
“…Available data showed the benefits of resistance training programs when combined with sport-specific training in youth [4][5][6]. For example, significant strength and *Address correspondence to this author at the Center of Research, Education, Innovation and Intervention in Sport (CIFI 2 D), Faculty of Sport, University of Porto, Porto, Portugal; Tel: +351 964663997; Fax: +351 225500689; E-mail: rojapon@hotmail.com physical performance improvements of adolescent soccer players were reported when combined with specific soccer and resistance training programs [4]. Plyometric training studies in youth reported changes in various types of performance such as in vertical jump, sprint, agility, and sprint cycling tests following training programs [7,8].…”
Section: Introductionmentioning
confidence: 99%